Використання систем підтримання рішень з екологічної безпеки для моделювання забруднення атмосфери внаслідок хімічних аварій - Kovalets, Ivan; Bespalov, Viacheslav; Maistrenko, Svitlana; Udovenko, Oleg (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2022)
We studied the possibility of the combined application of screening models to assess the characteristics of sources in accidents at storage facilities for hazardous substances with complex models of atmospheric transport as part of modern decision support systems to calculate air pollution in a wide range of spatial and temporal scales. The evaporation time following an emergency spill, estimated by screening models, is used to set the emission intensity and calculate the atmospheric transport by the RODOS nuclear emergency response system. For the accident in Chernihiv on March 23, 2022, it was estimated that the maximum permissible concentration of ammonia 0.2 mg/m3 was exceeded at distances up to 75 km from the source. The dependence of the calculated maximum concentrations on time is close to asymptote cmax ~ t-4.5 up to 15 h after emission, which is consistent with the asymptote σ ~ t3/2 for the time dependence of the sizes of puffs following turbulent dispersion of instantaneous releases.